Retrospective review of the use of as-needed hydralazine and labetalol for the treatment of acute hypertension in hospitalized medicine patients. (January 2018) - Gaynor, Michelle F.; Wright, Garth C.; Vondracek, Sheryl
Background: The aim of this study was to evaluate the use of as-needed (PRN) labetalol and hydralazine [intravenous (IV) or oral] in hospitalized medicine patients for the treatment of severe asymptomatic hypertension and to examine the potential negative outcomes associated with their use. Methods: The electronic health record of 250 medicine patients hospitalized at the University of Colorado Hospital between November 2014 and April 2016 who received at least one dose of PRN IV or oral hydralazine or labetalol were retrospectively reviewed. The primary outcome was to describe the use of PRN antihypertensive medications in this population. Results: A total of 573 PRN doses of antihypertensive medication were administered. Oral hydralazine was the most common (521 doses, 90.9%). A total of 36% of PRN administrations were given for a systolic blood pressure (SBP) <180 mmHg and diastolic blood pressure (DBP) <110 mmHg (cut-point for acute severe hypertension). No serious adverse events were related to PRN antihypertensive administration. Despite receiving at least one PRN antihypertensive medication during hospitalization, 40.8% of patients were not continued on their home antihypertensive medication(s) while hospitalized, and 62.4% of patients did not have their home regimens intensified at discharge. Conclusion: As-needed oral hydralazine is frequently prescribed for acute blood pressure lowering with administration thresholds often less than what are used to define acute severe hypertension. Many patients are prescribed PRN antihypertensive medication instead of being continued on their home regimens, and most patients do not have the intensity of their home regimens increased. Providers need to be educated about the use of PRN antihypertensive medication for the management of severe asymptomatic hypertension in the hospital setting.